Comparison of Macular Findings due to Vitreomacular Traction Alone or in Association with Epiretinal Membrane. Issue 1 (January 2017) - Chatziralli, Irini; Theodossiadis, George; Grigoropoulos, Vlassis; Datseris, Ioannis; Chatzirallis, Alexandros; Theodossiadis, Panagiotis
Purpose: To evaluate the anatomical and functional findings in patients with vitreomacular traction (VMT) alone or in combination with epiretinal membrane (ERM). Methods: In this retrospective, cross-sectional study, we studied 102 patients with VMT, either alone (n = 37) or combined with ERM (n = 65). All patients were examined with spectral-domain optical coherence tomography (SD-OCT). We recorded the vitreofoveal angle of VMT nasally and temporally, the horizontal diameter of VMT, macular thickness, the presence, type, and location of macular edema, the ellipsoid zone (ΕΖ)/external limiting membrane (ELM) status, and the visual acuity. Results: Patients with VMT combined with ERM presented smaller vitreofoveal angle nasally and temporally, broader adhesion diameter, and a greater extent of EZ defect compared to patients with VMT alone, although there was no statistically significant difference in EZ and ELM condition regarding the number of affected cases. There is also no statistically significant difference between the 2 groups concerning the visual acuity. In the majority of patients with VMT alone, cystoid macular edema was present mainly at the foveal area. In cases where VMT coexisted with ERM, macular edema was mostly found to be diffuse, while cystoid or mixed type, extending to the whole macular area, was also present. Conclusions: Patients with VMT in association with ERM have different characteristics in SD-OCT compared to those with VMT alone regarding the type and location of macular edema, the extent of EZ defect, as well as the vitreofoveal angle and the VMT diameter. Moreover, they presented worse visual acuity compared to those with VMT alone, although the difference did not reach statistical significance.